28.2k views
0 votes
Find the general solution to 2y ′′ − y ′ − y = 0.

User Ridox
by
5.0k points

1 Answer

1 vote

Answer: y(x) =
C_(1) e^(x) + C_(2) e^{(-x)/(2) }

Explanation:

2y ′′ − y ′ − y = 0

The characteristic equation is:


2r^(2) - r - 1 = 0


2r^(2) - 2r + r - 1 = 0

2r(r-1) + 1(r-1) = 0

(r-1)(2r+1) = 0


r_(1) = 1 , r_(2) = (-1)/(2)

∴ there are two distinct roots

so the general equation is as follows:

y(x) =
C_(1) e^{r_(1)x } + C_(2) e^{r_(2)x }

y(x) =
C_(1) e^(x) + C_(2) e^{(-x)/(2) }

User Proninyaroslav
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.